The Effect of Filler on the Quality of Snack Food Extruded from Solid Matter of Industrial Soybean Tofu - Salahudin, Farid; Syamsixman, Syamsixman (Biopropal Industri, 2010)
Tofu filter cake is the waste of tofu processing which is used for animal feed. In the other hand tofu filter cake can be used at extruded food processing. The purpose of this study is to look for the formulas and filler materials which could produce extruded food. The first variable in this research is the kind of corn that is pop corn and maize corn. The second variable is formulas of filler material that is composition of corn: rice: tofu filter cake = 1:1:0.5; 1:1:0.25; 1:2:0.5 and 1:2:0.25. The result is the formula which can produce best extruded food is pop corn: rice: tofu filter cake = 1:2:0.25 with Expansion Ratio (ER) 2.22 and protein content 8.83%.